Promoting disaster preparedness for children with special healthcare needs: A scoping review - Maya Newman; Carl Froilan D. Leochico (Elsevier, 2022)
The rise in the global temperature from greenhouse gases linked to human activities have influenced the increase in frequency of natural disasters, including hurricanes, tropical cyclones, floods, wildfires, and droughts. Children with special healthcare needs (CSHCN) are particularly susceptible to extreme weather events. Disaster planning for CSHCN is an important public health issue. The aim of this study is to contribute to the limited body of literature related to the climate crisis and CSHCN, and to summarize possible ways to improve the disaster preparedness of families of CSHCN. Using OVID Medline, Embase, Cochrane Library and Joanna Briggs Institute, a scoping review of studies from 2011 to 2021 related to climate change and disability was conducted. After screening, 242 articles were captured and eight articles on pediatric disaster preparedness for CSHCN were analyzed. Several studies assessing emergency preparedness knowledge of families with CSHCN demonstrated that the majority do not have a disaster kit, emergency plan, information cards, or awareness of a shelter. One study showed no difference in preparedness of families with CSHCN in two geographic regions prone to different natural disasters. Two studies evaluated families with CSHCN dependent on electricity for survival and less than 50% had battery backups for prolonged power failure. Families of CSHCN are generally underprepared for a natural disaster, regardless of the type of disaster. Based on the included studies, the following improved the level of preparedness of families with CSHCN: disaster preparedness education, an emergency kit, an eight-item checklist provided in the emergency room, a clinic nurse coordinator, as well as programs and policies that improved social support, self-efficacy, and resilience.